Description of Children's Readiness to Enter Elementary School in Class 1 Students of SD Negeri Jabon District: Gambaran Kesiapan Anak Masuk Sekolah Dasar Pada Siswa Kelas 1 SD Negeri Kecamatan Jabon - Febrianti, Aisyah Mawaddah; Mariyati, Lely Ika (Indonesian Journal of Education Methods Development, 2023)
This descriptive quantitative research aimed to investigate the readiness of grade 1 elementary school students to enter primary education in the Jabon sub-district. A sample of 102 students out of a total population of 110 was selected using non-probability accidental sampling. Data analysis, employing the SPSS 17.0 for Windows program, involved descriptive statistics to assess school readiness based on measures such as mode, mean, median, standard deviation, and variance range. The findings revealed that among grade 1 students at SD Jabon Sidoarjo District, 85.3% (87 students) exhibited high readiness, 8.8% (9 students) demonstrated sufficient readiness, and 5.9% (6 students) displayed less readiness to enter elementary school. These results shed light on the preparedness of children for formal education and have implications for educational stakeholders in fostering optimal learning environments and supporting students' smooth transition to elementary school. Highlights: The study examined the readiness of grade 1 students to enter elementary school, providing insights into their preparedness for formal education. A significant majority of grade 1 students (85.3%) demonstrated high readiness, emphasizing the positive foundation for their academic journey. The findings have implications for educational stakeholders, highlighting the importance of creating supportive learning environments and facilitating a smooth transition into elementary school. Keywords: Readiness, Elementary school, Grade 1 students, School transition, Educational implications.